STUDENTS’ PERCEPTION TOWARDS THE USE OF WEBTOON TO IMPROVE READING COMPREHENSION SKILL - Wike Idola Erya; Reza Pustika (Journal of English Language Teaching and Learning, 2021)
This research discussed about student’s perception on the use of Webtoon to improve reading comprehension skill. Webtoon is a new platform that can be used to improve reading skill by its words used and interesting pictures. The purpose of this study is to explain whether or not Webtoon can increase students’ interest in reading comprehension skill. The respondents of the study are the students of English Education students at Universitas Teknokrat Indonesia.The result of the study indicates that the students are more interested and get the motivation to improve their reading comprehension skill by using Webtoon.